Tradisi Ngalangkang Pambak pada Umat Hindu Kaharingan di Kecamatan Katingan Hilir Kabupaten Katingan (Kajian Agama Budaya dan Psikologi) - Eka, Nali; Megawati, Megawati; Wiranata, Anak Agung Gede; Vienlentia, Raisa (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Abstract The death ceremony carried out by Hindu Kaharinngan in Katingan Hilir consists of the stages of the burial ceremony: Tiwah and Ngalangkang Pambak. This ceremony is a mandatory follow-up after the Tiwah, but in reality, Ngalangkang Pambak is no longer held after the ceremony. This ceremony is even carried out as an annual ritual or to commemorate certain events. This research uses a qualitative method with a case study approach. The type of data for this research is primary data sourced from informants and secondary data sourced from supporting data. Data collection methods include observation, interviews, recording, and documentation studies. Data analysis and interpretation procedures in research using a